Prispevek Cerkve k slovenski narodnostni istovetnosti - Juhant, Janez (Traditiones (Ljubljana), 1997)
Slovene national identity is linked to the Church which was the mainstay of national life, especially since the Slovenes did not have a state of their own. Within the Church the Slovenes cultivated their language, while Catholic priests (cautiously) articulated their national demands. Leading Catholic personalities played a decisive role in the movement for the secession of Slovenes and other South Slavs from Austria. necause of its supremacy in the national movement, the Church came into conflict first with liberal, then with communist forces, whicli wanted to tear the people away from the Church and submit it to their rule. In spite of these pressures, the Church has helped shape Slovenia's identity, linguistic and national as well as political.
Keywords: Catholic Church; katoliška cerkev; Slovenia; Slovenija; narodnostno vprašanje